Hunting badger - Hillerman, Tony (Hillerman, Tony. Leaphorn & Chee novel., 1999)
Crime busters Leaphorn and Chee are back together on a case and at odds with the FBI in a great addition to Tony Hillerman's acclaimed series. A pre-dawn raid on the Ute tribe's gambling casino leaves one policeman dead, a deputy sheriff wounded and the criminals vanished into the maze of canyons on the Arizona border. The FBI take over the manhunt, but the high-tech investigation grinds to a halt in this unusual territory. It is not until Chee and Leaphorn arrive on the scene that the connection to a famous Ute legend enables the solution to the case.